Peran Pendidikan Geografi dalam Mewujudkan Pendidikan untuk Pembangunan Berkelanjutan - Oraby, Ghada Abd Elsattar Mohammed (PT. Pubsains Nur Cendekia, 2026)
Education for Sustainable Development (ESD) has emerged as a central strategy for addressing interconnected environmental, social, and economic challenges under Sustainable Development Goal 4. While geography education is widely acknowledged as inherently aligned with sustainability principles, limited analytical attention has been given to the structural conditions that shape its transformative capacity. This study critically examines the role of geography education in advancing ESD within contexts marked by persistent educational inequalities. Using a qualitative and conceptual research design based on systematic document analysis of academic literature and international policy reports (2010–2024), the study synthesizes evidence on sustainability competencies, spatial pedagogy, and global education disparities. The findings indicate that geography education contributes to the development of systems thinking, anticipatory competence, normative reflection, and strategic action through spatial inquiry, place-based learning, and geospatial tools. However, its effectiveness is structurally mediated by inequalities in access, teacher preparation, curriculum flexibility, and institutional support. The study advances a conceptual framework positioning geography education as a mediating structure between educational inequality and sustainability competence formation. It concludes that strengthening geography pedagogy, teacher capacity, and equitable institutional conditions is essential for translating ESD from policy aspiration into transformative educational practice.